Utilization of Extract of Sambang Getih Leaves (Hemigraphis colorata. Hall. F) as a Acid-Base Indicator - Eksari Ekasari; Purnama Ningsih (Jurnal Akademika Kimia, 2020)
Getih sambang leaves (Hemigraphis Colorata. Hall. F) are plants that have a distinctive and unique color, namely the upper surface of the leaf is green and the bottom of the leaf is burgundy where sambang leaves contain anthocyanin compounds. Anthocyanin is the color pigment in plants that forms the basis of the use of natural indicators. This study aims to prove whether getih cucumber leaves can be used as an acid-base indicator, to determine the type of acid-base titration that is suitable for indicators of getih cucumber leaves, and to find out what the pH-changing color route of getih cucumber leaves is. The method used is extraction, namely maceration. Wee leaves are macerated by using methanol as a solvent for 24 hours. The extract was previously tested using HCl solution and NaOH solution as a test to prove the presence of anthocyanin. The results obtained in this study, getih sambang leaf extract can be used as an indicator of acid base, and also the type of acid-base titration that is suitable for use in the indicator of getih leaf extract extract precisely on the titration of strong-base strong acid, and strong weak base-acid It is best used as a substitute for the phenolphthalein indicator. In titration of strong and weak acids and bases, it is good to be used as a substitute for the indicator of methyl orange. The pH range obtained from the getih sambang leaf extract is pH 4-7 (red-purple).